Influence of drying temperature on properties of wood surfaces - Šernek, Milan (Zbornik gozdarstva in lesarstva, 2002)
This article deals with modifications of wood surface properties induced by different drying temperatures. The aim of the study was chemical and physical characterization of a wood surface concerning low and high temperature exposure. Additionally, the correlation between the chemical composition of a wood surface and its wetting capacity were investigated. X-ray photoelectron spectroscopy and contact angle measurements were conducted. Two wood species, yellow poplar (Liriodendron tulipifera) and southern pine (Pinus taeda) were studied. The results showed that the percentage of carbon increased with drying temperature, and consequently, the percentage of oxygen decreased. The samples exposed to high drying temperatures indicated a higher content of extractives on the wood surface. These samples exhibited the highest contact angle and the lowest wettability
Keywords: les; površina; sestava; sušenje; vpliv temperature